Morphological Variation of Durio kutejensis (Hassk.) - Priyanti, Priyanti; Chikmawati, Tatik; Sobir, Sobir; A. Rifai, Mien; Hartana, Alex (Proceeding International Conference on Global Resource Conservation, 2013)
Durio kutejensis (Hassk.) Becc. (lai) is a cultivated plant in Genus Durio except D. zibethinus Murr. (Durian). D. kutejensis is superior than D. zibethinus based on blunt spine, not fragrant, flashy color (dark yellow to orange) and storage ability up to 7-8 days. The aim of this research was to analyze the variation of morphological characters of 31 landrace trees which was collected from Batuah Village, Tanah Merah Village and Sebulu Village in East Kalimantan. Lai varied in several characters which were their crown shape, branch type, leaf shape, flower color, and fruit shape. The crown shape is pyramidal, semi circular, oblong, and umbrella. The branch types are spreading or erect to rather spread. The leaf shape is oblong, lanceolate or elliptic. The flower has pink or dark red color. The shape of fruit is globose, globose with 5-lobed, ovoid with 5-lobed, and oblong with 5-lobed. Key words: Durio kutejensis, morphology variation, superior